An integrated framework for service quality, choice overload, customer involvement and satisfaction: Evidence from India's non-life insurance sector. Issue 4 (15th October 2019) - G., Rejikumar; Sreedharan V., Raja; Saha, Raiswa
Abstract : Purpose: Consumer behavior, in the context of general insurance, is worth exploring to formulate growth strategies for insurance sector in India in light of the proposed structural changes. Indian consumers attract global players due to untapped potential and favorable policy measures initiated for higher foreign direct investments. The purpose of this paper is to understand the prevailing level of service quality as perceived by insurance customers in India in the presence of certain contextual antecedents and moderators. Design/methodology/approach: Perceptions about constructs like customer risk dispositions, awareness, past experiences, customer involvement, choice overload, service quality and satisfaction of 256 customers were collected using a questionnaire survey. A variance-based structural equation modeling helped to identify significant linkages among the constructs. Findings: In order to assess service quality levels, a 15-item scale having the infrastructure, employees, agents and product dimensions was found valid and reliable. Choice overload and customer involvement were found to moderate the influence of antecedents and service quality, respectively. The influence of choice overload on quality perceptions is insignificant. The study concludes that the existing risk beliefs are insufficient, and experiences have less predictive contribution to quality perceptions. Research limitations/implications: Theoretically, this study examined the process of satisfaction development from service quality perceptions. This study offers insights for developing theories to portray future consumer behavior where more dependence of self-service technologies is expected to dominate service delivery mechanisms in insurance. The study informs that general insurance customers in India prefer more diversified products, more customer-centric employees/agents and better technical quality. Practical implications: The findings of this study contribute to the understanding of the prevailing insurance consumer behavior in the general insurance sector of India and help insurance service providers in streamlining their strategies for better insurance penetration and reduced lapse rate. Originality/value: This study helps in understanding the emerging trends in general insurance buying behavior in India.